An Evolutionary Approach to Single-sided Ventilated Façade Design. (2017) - Marzban, Samin; Ding, Lan; Fiorito, Francesco
Abstract: A significant portion of the carbon and greenhouse gas emissions of residential buildings in Australia is associated with energy consumption for comfort and health. This study aims to reduce the carbon emissions of residential buildings by optimizing façade design. Targeting to minimize thermal loads, mechanical ventilation will be substituted by natural ventilation, meanwhile indoor environments and appropriate visual comfort will be improved. An evolutionary approach based on a Genetic Algorithm (GA) is developed to determine a set of optimal solutions of façade design for the performance targets of ventilation efficiency, energy consumption, and visual comfort. The proposed approach comprises: an evolutionary process model; the genetic representation of single-sided façade design; genetic operation methods; and fitness functions of multi-objective performance targets as well as Pareto evaluations. The process model enables mapping of façade design options and performance targets to evolve over time. Ventilation, energy and comfort analysis of single-sided ventilation are conducted for the evaluation of the resulting performance of façade design. The expected research outcomes will improve low carbon façade design of residential buildings while reducing cooling and heating costs for the construction industry and the consumer.